2007
DOI: 10.1158/0008-5472.can-07-0589
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor (EGFR) Ubiquitination as a Mechanism of Acquired Resistance Escaping Treatment by the Anti-EGFR Monoclonal Antibody Cetuximab

Abstract: Cetuximab is an epidermal growth factor receptor (EGFR)-blocking antibody that has been approved for treatment of patients with metastatic colorectal cancer. In this study, we investigated biochemical changes in signaling pathways of a cetuximab-resistant subline of DiFi colorectal cancer cells (DiFi5) that was developed by exposing the parental sensitive cells to subeffective doses of cetuximab over an extended period of time. Compared with parental DiFi cells that express high levels of EGFR and in which cet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
134
5
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 24 publications
(37 reference statements)
6
134
5
1
Order By: Relevance
“…170 These findings were confirmed using immunofluorescence (IF) microscopy and flow cytometry. In contrast to the study by Lu et al 168 this study demonstrated that EGFR does not seem to be associated with c-Cbl in cetuximabresistant lines, while the parental cetuximab-sensitive line maintains this association. These data support a previously published mechanism for EGFR degradation via c-Cbl recruitment to tyrosine 1045.…”
Section: Mechanisms Of Resistance To Egfr Targeted Antibodiescontrasting
confidence: 99%
“…170 These findings were confirmed using immunofluorescence (IF) microscopy and flow cytometry. In contrast to the study by Lu et al 168 this study demonstrated that EGFR does not seem to be associated with c-Cbl in cetuximabresistant lines, while the parental cetuximab-sensitive line maintains this association. These data support a previously published mechanism for EGFR degradation via c-Cbl recruitment to tyrosine 1045.…”
Section: Mechanisms Of Resistance To Egfr Targeted Antibodiescontrasting
confidence: 99%
“…The finding that Src family kinases are sufficient to modify EGFR dependence is in line with considerable evidence linking EGFR activity with this family: c-Src itself has been characterized extensively with respect to its cooperative relationship with EGFR (27), and the introduction of dominant-active c-Src can reduce the inhibitory effects of erlotinib in head and neck squamous cell carcinoma models (28). Src family kinase activation has been observed in cetuximab-resistant colorectal adenocarcinoma and NSCLC squamous cell carcinoma in vitro models (29,30), and it has been reported that CRIPTO1-mediated EGFR TKI resistance in NSCLC is Src-dependent (31). Furthermore, a recent report described increased expression and activation of Src, mediated by integrin activation, in EGFR TKI-resistant lung adenocarcinoma models (32).…”
Section: Discussionmentioning
confidence: 59%
“…To investigate mechanisms driving cetuximab resistance in SCCUAT, we established cetuximab-resistant clones of two of the most sensitive cell lines, HN5 and FaDu, by continuous cetuximab pressure in vitro and in vivo, respectively. It has previously been demonstrated that acquired resistance to cetuximab can occur as a result of altered functional status of EGFR but that resistant cells remain fully or partially EGFR dependent (39,40). We therefore investigated the status of EGFR in the resistant cells.…”
Section: Discussionmentioning
confidence: 98%